PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KOPI NESCAFE DI JAKARTA PUSAT - Ruminta, Darkiman; Indrarti, Wahyu - (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to determine the direct influence of brand awareness, brand associations, perceived quality and brand loyalty on the purchasing decisions of Nescafe coffee consumers in the Jakarta area. This research uses quantitative statistical research, collecting data in the field using survey methods. Distribution of questionnaires is used to find out respondents' answers regarding the relationship between the independent variable and the dependent variable. The independent variables in this research are brand trust, product quality, and word of mouth, while the dependent variable is purchasing decisions. Based on the results of the analysis and discussion that has been carried out, it can be concluded that; Partial brand awareness does not have a significant impact on the decision to purchase Nescafe coffee. Brand association does not partially have a significant impact on Nescafe coffee purchasing decisions. Partial quality perceptions have a significant impact on the decision to purchase Nescafe coffee. Partial brand loyalty shows that there is no significant relationship to the dependent variable, namely purchasing decisions. Brand awareness, brand association, perceived quality and brand loyalty together (simultan) have a significant influence on the decision making process of purchasing Nescafe coffee. Keywords: Coffee, Brand, Purchase Decision